2009
DOI: 10.3341/kjo.2009.23.2.114
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Radiation Retinopathy of Left Eye After Radiation Therapy of Right Brain Metastasis

Abstract: A 37-year-old female, who had received modified radical mastectomy for cancer of her right breast, presented with decreased visual acuity in the left eye after radiation therapy for the management of the metastasis to her right brain 14 months ago. After ocular examination, we diagnosed her as radiation retinopathy. At the time of the first visit, the corrected best visual acuity was 0.4 in the left eye, and fundus examination revealed cotton wool spots and cystoid macular edema (CME). The findings in the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The authors stated that this was the lowest retinal dose of radiation documented to produce retinopathy. Hong et al 3 described a case of a 37-year-old female with breast cancer that metastasized to the brain who received 30 Gy over 10 fractions WBRT and 12 Gy local boost irradiation to the tumor bed in the right frontal area. Interestingly, the patient developed radiation retinopathy predominantly affecting the left eye; the authors suggested that shielding also be provided contralateral to the site of irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that this was the lowest retinal dose of radiation documented to produce retinopathy. Hong et al 3 described a case of a 37-year-old female with breast cancer that metastasized to the brain who received 30 Gy over 10 fractions WBRT and 12 Gy local boost irradiation to the tumor bed in the right frontal area. Interestingly, the patient developed radiation retinopathy predominantly affecting the left eye; the authors suggested that shielding also be provided contralateral to the site of irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than a dozen cases of radiation retinopathy from WBRT have been reported. [3][4][5][6][7][8] Only a single case report has been published describing radiation retinopathy after a dose of 30 Gy in 10 fractions. 5 The patient was a 55-year-old female with metastatic breast carcinoma who developed vision loss 6 years after treatment.…”
Section: Introductionmentioning
confidence: 99%